Price convergence and information efficiency in German natural gas markets - Christian Growitsch; Marcus Stronzik; Rabindra Nepal (Institute of Energy Economics at the University of Cologne (EWI), 2012)
In 2007, Germany changed network access regulation in the natural gas sector and introduced a so-called entry-exit system. The re-regulation's spot market effects remain to be examined. We use cointegration analysis and a state space model with time-varying coefficients to study the development of natural gas spot prices in the two major trading hubs in Germany and the interlinked Dutch spot market. To analyse information efficiency in more detail, the state space model is extended to an error correction model. Overall, our results suggest a reasonable degree of price convergence between the corresponding hubs. However, allowing for time-variant adjustment processes, the remaining price differentials are only partly explained by transportation costs, indicating capacity constraints. Nonetheless, market efficiency in terms of information processing has increased considerably among Germany and The Netherlands.
Keywords: C32; G14; L95; 330; natural gas market; regulation; cointegration; price convergence; time-varying coefficient